Kecemasan Sosial dengan Kecanduan Game Online Pada Remaja - Rusyanto, Joseph Kaleb; Purnomo, Jusuf Tjahjo (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
The background to this research is that there is a contradiction in the findings of the relationship between social anxiety and online game addiction in previous research. The aim of this research is to find out whether there is a positive and significant relationship between social anxiety and online game addiction in adolescents. This research uses a quantitative descriptive approach. The subjects of this research are teenage online game players. In this study, a sample size of 101 teenage respondents was used. The data collection technique for this research was carried out by distributing questionnaires. The data analysis technique in this research uses descriptive analysis, classical assumption tests, and interventional analysis using correlation tests. Data collection tools were the La Greca social anxiety scale with 18 items and the Ulkhaq online game addiction scale with 21 items. Data analysis uses Pearson's product moment correlation technique. The correlation test results show r = 0.494 with a p value = 0.000 (p <0.005) which means there is a significant positive relationship between social anxiety and online game addiction.